Desnitrificação de efluente de abatedouro de tilápia utilizando manipueira como fonte de carbono - Kummer, Ana Carolina Barbosa (2008)
The processing fish industry is responsible for the production of high amounts of wastewater, rich in organic matter, grease and high concentration of nitrogen, so, conventional use of primary and secondary treatment is not enough to reach the standard demand from the environmental agencies. Consequently, it is necessary the application of wastewater treatment techniques to reduce the impacts produced by those effluents on the environment. The biological treatment of nitrogen compounds has been an alternative to improve their quality. One of the biological processes is based on nitrification followed by denitrification, where oxidized compounds by nitrogen are transformed in molecular nitrogen that rises to the atmosphere. This trial aimed at checking the denitrification of tilápia wastewater from slaughterhouse, in a batch reactor. So, the wastewater from a cassava processing industry (manipueira) was evaluated as a carbon source, as well as the shaking conditions of the process. The experiments were carried out in laboratory series. Five shaking levels were tested (20; 32; 60; 88 e 100 rpm) as well as five COD/N ratio levels (0.1; 1.0; 3.2; 5.4 and 6.3), forming a planning as a Central Composite Rotational Design (CCRD), with four essays in levels +1 and -1; four essays on the axial points levels (-1.414 and +1.414) and one more triplicate in the central point (0), which meant 11 (eleven) essays. The denitrification performance through the nitrate removal (%) and COD removal (%) were evaluated. During this process, temperature (°C), pH and alkalinity (mgCaCO3.L-1) were also observed. The results showed that the COD/N ratio had significant influence, with a 95 % of confidence interval on the process of nitrate and nitrite removal, with a great operation range, from 3.2 to 5.4, whose nitrogen removal efficiencies were 100 %. On the other hand, shaking did not have a significant effect on the process.